Gymnothorax poikilospilus, a new moray eel (Teleostei: Anguilliformes: Muraenidae) from Penghu Islands, western Taiwan - Huang, Wen-Chien; Loh, Kar-Hoe; Chen, Hong-Ming (Zootaxa, 2022)
Gymnothorax poikilospilus sp. nov. is described based on two specimens collected from Penghu Islands, western Taiwan. It is a medium-sized brown moray that body covered with several rows of inconspicuous large dark brown patches on the back of body and dorsal fin. It has slightly elongated and arched jaws similar to the common characteristic of the genus Enchelycore Kaup, but the dentition supports it belongs to typical morays of the genus Gymnothorax Bloch. The new species can be distinguished from other similar Indo-Pacific brown morays by the combination of dentition, vertebral formula, and morphometric measurements. Molecular analyses based on 612 bp of mitochondrial COI gene also support it as a distinct species.